Limites e fronteiras : perspectivas emancipatórias no povoado São José da Caatinga em Japaratuba, Sergipe - Ribeiro, César Augusto França (2018)
We start from the assumption that the current forms, delimitations, limits and borders of the current Brazilian territorial network result from a long process of changes. In this context, the creation of municipalities is a theme that generates endless reflections, given the geographic, political and social character intrinsically found in this theme. In order to contribute to this theme, we propose to analyze the political and daily relations that enable or not the emancipatory intentions in the town of São José da Caatinga in Japaratuba / SE. To do so, we have specific objectives to understand the origins and socio-spatial evolution of the village; to understand the transformations in the laws that deal with municipal emancipation and its implications in the Sergipe territorial network; understand the political-juridical and symbolic-cultural bases that support the demands of emancipation; compare the intended boundaries with the political-administrative boundaries. We use the hermeneutic-phenomenological approach anchored in Heidegger (1989, 2003, 2015), so that it becomes possible to understand the daily relations of the villagers and their territorial aims. The reflections of this study are supported in the territory category, having as main theorists Raffestin (1993) for the analysis of the relations of power; Cigolini (2012), Cataia (2001) and Ratzel (1990) for political-institutional reflections; Dardel (2015), Bonnemaison (2002) and Holzer (1997) for symbolic-identity reflections. Methodologically, the case study was used as a qualitative approach to understand emancipatory phenomena in a particular way in the village. Based on the above, we consider that both the power of constitutional political language and daily relations can build territories in the geographical space. On the one hand, there is the institution of the municipal territory, on the other hand the 'delimitation' that is surrounded by symbolic and identity relations that generate brands in the territory.